Failure in Asthma Control: Reasons and Consequences - Fulvio Braido (Scientifica)
Clinical research showed that asthma control is an achievable target. However, real-life observations suggest that a significant proportion of patients suffer from symptoms and report lifestyle limitations with a considerable burden on patient’s quality of life. The achievement of asthma control is the result of the interaction among different variables concerning the disease pattern and patients’ and physicians’ knowledge and behaviour. The failure in asthma control can be considered as the result of the complex interaction among different variables, such as the role of guidelines diffusion and implementation, some disease-related factors (i.e., the presence of common comorbidities in asthma such as gastroesophageal reflux disease (GERD), sleep disturbances and obstructive sleep apnea (OSA), and rhinitis) or patient-related factors (i.e., adherence to treatment, alexithymia, and coping strategies). Asthma control may be reached through a tailored treatment plan taking into account the complexity of factors that contribute to achieve and maintain this objective.